Green synthesis of Fe/Cu oxides composite particles stabilized by pine needle extract and investigation of their adsorption activity for norfloxacin and ofloxacin. Issue 9 (14th July 2021) - Ma, Peili; Liu, Qiujie; Liu, Penglei; Li, Hongping; Han, Xiuli; Liu, Lie; Zou, Weihua
Abstract: Iron, copper oxides composite particles (Fe/Cu oxides CPs) were produced using rapid, single-step, green and sustainable pathway from biomolecules of pine needle extract and were adopted as a potential adsorbent for the removal of norfloxacin (NOR) and ofloxacin (OFLX) from aqueous solution. To understand the morphologies and properties of Fe/Cu oxides CPs, surface analysis via SEM image, EDS, TEM, XPS, BET and FTIR pattern were employed. The effects of factors such as contact time, reaction temperature, initial pH, initial concentration and ionic strength on the adsorption capacity of NOR or OFLX onto Fe/Cu oxides CPs were studied. Kinetic analysis confirmed that the kinetic data were well described by Double-constant rate equation. The experimental equilibrium data were well fitted by Redlich-Peterson, Koble-Corrigan and Dubinin-Radushkevich models and the maximum adsorption capacity of Fe/Cu oxides CPs calculated by Langmuir model for NOR and OFLX was 1.64 mmol/g and 1.26 mmol/g at 293 K, respectively. Thermodynamic parameters such as Gibbs free energy (ΔG), enthalpy (ΔH) and entropy (ΔS) were calculated and the results indicated that the NOR or OFLX adsorption onto Fe/Cu oxides CPs was spontaneous and endothermic. Adsorption mechanism of NOR and OFLX may be involved a combination of electrostatic interaction, the formation of hydrogen bonds, π-π stacking interactions, surface complexation, hydrophobic interaction. Graphical Abstract: